2018
DOI: 10.1177/1545968318770271
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Purposeful Head Movements During Community Ambulation Following Unilateral Vestibular Loss

Abstract: This study demonstrated that although walking at an adequate speed, individuals with UVH made fewer, smaller, and slower head movements symmetrically in both directions compared with healthy individuals and did not decouple their head movement relative to their trunk when required to make larger purposeful head turns during community ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…While we did not explicitly measure gaze, we speculate that subjects did their best to align their gaze direction with their voluntary head movement as instructed and that patients experienced poorer gaze stability during this task (e.g., 23 , 24 ). Indeed, recent studies have reported smaller and fewer yaw horizontal head turns during self-paced walking in patients after resection of vestibular schwannoma 25 , 26 . Again, we suggest that the principal response to deafferentation is the reduction in head movement amplitude and that reduced variability follows, rather than the reduction in variability being a direct effect of deafferentation.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not explicitly measure gaze, we speculate that subjects did their best to align their gaze direction with their voluntary head movement as instructed and that patients experienced poorer gaze stability during this task (e.g., 23 , 24 ). Indeed, recent studies have reported smaller and fewer yaw horizontal head turns during self-paced walking in patients after resection of vestibular schwannoma 25 , 26 . Again, we suggest that the principal response to deafferentation is the reduction in head movement amplitude and that reduced variability follows, rather than the reduction in variability being a direct effect of deafferentation.…”
Section: Discussionmentioning
confidence: 99%
“…Given this and the subjective nature of vertigo, enhanced and additional measures are needed, beyond the measurement of nystagmus. Future studies would benefit from the implementation of additional quantitative parametric measures such as posturography for measuring head kinematics and postural deviation, as endpoints during both early‐ and late‐phase recovery of vertigo (Gueguen et al, 2017; Paul et al, 2018). While the strain and gender of rats used for the pharmacokinetic study (male Wistar) was different from those used in the vestibular lesion model (female Long–Evans), the effect of this is likely to be minor due to the intravenous route of administration: A study comparing pharmacokinetics of ondansetron in male and female rats after oral and intravenous administration demonstrated only small differences after intravenous administration, while higher metabolism in male rats was suggested to underlie major differences after oral administration (Yang, Yang, & Lee, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deficits in vestibular function cause various disturbances in spatial orientation, gait, head movement, and upper body coordination. It was recently reported that patients with unilateral vestibular hypofunction reveal fewer, smaller, and slower head movements after surgery [3,4]. Additionally, these authors suggested that early referral for vestibular rehabilitation may be beneficial to improve the recovery of gait, dynamic stability, head movement, and upper body coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Such symptoms can cause changes in movement kinematics and compensatory alterations with respect to gait parameters [2]. For example, previous studies have reported significantly reduced head movement during both community ambulation (approximately ten minutes) [3] and during standardized gait testing of short duration [4]. Although such altered movement kinematics may also result in less efficient turning, the current clinical assessment of turning and its related outcome in patients with vestibular dysfunction are not validated.…”
Section: Introductionmentioning
confidence: 99%